RESTRICTION OF THE RIGHT TO INFORMATION IN THE INTERESTS OF NATIONAL SECURITY THROUGH THE FORMATION AND IMPLEMENTATION OF THE STATE INFORMATION POLICY: LEGAL AND ORGANIZATIONAL FRAMEWORK - Shynkar, Tetiana (Honor and Law, 2023)
Given the relevance and significance of the issue of restriction of the right to information, the article presents the results of the analysis of the current system of restriction of the right to information in the interests of national security. The author emphasizes that the State information policy is one of the most important components of the State national security policy. The subjects of formation of the State information policy are described as participants in the regulation of public relations of information exchange (regulatory activity) with an emphasis on the focus of their powers and functions on the subject-matter and practical tasks of public administration in general and, as a result, their participation in the formation and implementation of the relevant component of the State national security policy. The author analyzes the place and role of the National Security and Defense Council of Ukraine, the Cabinet of Ministers of Ukraine, public authorities in cooperation with local self-government bodies, the Center for Countering Disinformation and civil society institutions, the Ministry of Defense of Ukraine, as well as the defense forces, the Security Service of Ukraine, the Intelligence Agencies of Ukraine, and the National Council of Ukraine on Television and Radio Broadcasting in the formation and implementation of the State information policy. The activities of the Ministry of Culture and Information Policy of Ukraine are analyzed as the central executive body responsible for the formation and implementation of the state policy in the information sphere. Based on the analysis, the author formulates requirements for the subjects of formation and implementation of the state information policy.